Are current account deficits sustainable? New evidence from Iran using bounds test approach to level relationships - Hassan Heidari; Salih Turan Katircioglu; Narmin Davoudi (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
This paper provides new evidence on the long-run relationship between exports and imports of the Iranian economy by employing bounds testing approach to level relationships. In Iran, there have been many unusual policy changes and/or external shocks to the economy; this has resulted in the occurrence of a multitude of structural breaks in macroeconomic variables. By taking these breaks into account, results of the present study reveal that there is a long-run equilibrium relationship between imports and exports over the sample period, 1960-2007. This result confirms the finding of Arize (Imports and exports in 50 countries: Tests of cointegration and structural breaks, 2002) by employing bounds tests to level relationships and suggests that current account deficits in Iran are sustainable.
Keywords: C22; F10; F32; 330; current account; bounds test; Iran; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Import; Export; Kointegration; Strukturbruch; Schätzung; Iran